1999
DOI: 10.1021/jp991918j
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Study of Gas-Phase Proton Transfer in Ammonia−Hydrogen Halides and the Influence of Water Molecules

Abstract: The gas-phase proton-transfer reaction between ammonia and the hydrogen halides HF, HCl, and HBr and the influence of one, two, and three water molecules are investigated with high-level ab initio calculations on molecular clusters of NH 3 -HX-(H 2 O) n , n ) 0, 1, 2, 3 with X ) F, Cl, Br. Equilibrium geometries, dissociation energies, HX harmonic frequencies, and potential energy surfaces along the proton-transfer pathway of NH 3 -HX are calculated at the second-order Møller-Plesset perturbation (MP2) level w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 13 publications
4
29
0
Order By: Relevance
“…Advanced ab initio calculations by Tao and co-workers [161][162][163][164] support the formation and stability of NH4CI in the gas phase. The single NH3-HCI complex is hydrogen bonded only.…”
Section: Gas-phase Reaction Of Ammonia and Hydrochloric Acidmentioning
confidence: 95%
“…Advanced ab initio calculations by Tao and co-workers [161][162][163][164] support the formation and stability of NH4CI in the gas phase. The single NH3-HCI complex is hydrogen bonded only.…”
Section: Gas-phase Reaction Of Ammonia and Hydrochloric Acidmentioning
confidence: 95%
“…The acids studied include ammonium, [11][12][13] water, 14 hydrogen halides, 15,16 nitrous acid, 17 phenol, 18 and 7-hydroxyquinoline. 19 Our interests focus on ammonium-based strong oxidizers that can be used in rocket propellants, motivated by the practical need to find more environmentally benign oxidizers than the commonly used ammonium perchlorate.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been carried out on microsolvation in water with alkali halides and hydrogen halides. 26–37 It is known that nine water molecules are needed to solvate a NaCl molecule36, 37 where it acquires the ionic structure Na + Cl − . Jungwirth37 has shown that NaCl acquires the ionic structure even on microsolvation in a cluster of six water molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Jungwirth37 has shown that NaCl acquires the ionic structure even on microsolvation in a cluster of six water molecules. Tao et al 27 have performed high‐level ab initio calculations on the binding of one, two, and three water molecules with HF, HCl, HBr, and NH 3 . In this study, to form the complexes involving two and three water molecules, they have added each water molecule separately.…”
Section: Introductionmentioning
confidence: 99%